Cortical Thickness in Adolescents with a Family History of Alcohol Use Disorder. (6th December 2017) - Henderson, Kate E.; Vaidya, Jatin G.; Kramer, John R.; Kuperman, Samuel; Langbehn, Douglas R.; O'Leary, Daniel S.
Abstract : Background: Individuals with a family history (FH+) of alcohol use disorder (AUD) have a higher risk for developing an AUD than those with no family history (FH−) of AUD. In addition, FH+ individuals tend to perform worse on neuropsychological measures and show heightened impulsivity, which may be due to underlying differences in brain structure such as cortical thickness. The primary aim of this study was to investigate differences in cortical thickness in FH+ compared to FH− adolescents. Secondary aims were to (i) investigate differences in executive functioning and impulsivity, and (ii) examine associations between brain structure and behavior. Methods: Brain scans of 95 FH− and 93 FH+ subjects aged 13 to 18 were obtained using magnetic resonance imaging. FH+ subjects were required to have at least 1 biological parent with a history of an AUD. FH+ and FH− individuals had limited or no past alcohol use, thereby minimizing potential effects of alcohol. Subjects were evaluated on impulsivity and executive functioning tasks. Thicknesses of cortical lobes and subregions were analyzed using FreeSurfer. Regions showing group differences were examined for group‐by‐age interactions and correlations with neuropsychological and personality measures. Results: FH+ adolescents had thinner cortices in frontal and parietal lobes, notably in the medial orbitofrontal, lateral orbitofrontal, and superior parietal cortices. The difference in cortical thickness between family history groups was strongest among the youngest subjects. FH+ subjects were also more impulsive and had poorer performance on a spatial memory task. Conclusions: These findings demonstrate frontal and parietal structural differences in FH+ adolescents that might underlie cognitive and behavioral characteristics associated with AUD risk. Abstract : Individuals with a family history (FH+) of alcohol use disorder (AUD) have a higher risk for developing an AUD than those with no family history (FH−) of AUD. In addition, FH+ individuals tend to perform worse on neuropsychological and impulsivity measures, potentially due to underlying differences in brain structure. This study found that FH+ adolescents had thinner frontal and parietal cortices than FH−, suggesting that frontal and parietal structural differences might underlie cognitive and behavioral characteristics associated with AUD risk.